2017
DOI: 10.1097/fpc.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and pathway analysis of left ventricular function after anthracycline exposure in adults

Abstract: Background Anthracyclines are important chemotherapeutic agents, but their use is limited by cardiotoxicity. Candidate gene and genome-wide studies have identified putative risk loci for overt cardiotoxicity and heart failure, but there has been no comprehensive assessment of genomic variation influencing the intermediate phenotype of anthracycline-related changes in left ventricular (LV) function. The purpose of this study was to identify genetic factors influencing changes in LV function after anthracycline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…It has been shown that the maximum reduction of LV function has been associated with the following SNPs in those patients treated with trastuzumab: LDB2 (limb domain binding 2), BRINP1 (BMP/retinoic acid inducible neural-specific protein 1, a suppressor of cell cycle progression), RAB22A (a member of the RAS oncogene family which is key in endocytic trafficking), TRPC6 (transient receptor potential cation channel subfamily C member 6, involved in cardiac remodelling and hypertrophic cardiomyopathy), LINC01060 (a long intergenic noncoding RNA) and chromosome 6 intergenic region. Another GWAS involved a cohort of 385 patients identified targets which have been confirmed to be present in 181 patients [141]. This includes a SNP near PR domain containing 2, with ZNF domain (PRDM2), which is involved in DNA double-strand break and repair of oxidative stress.…”
Section: Insights On Potential New Biomarkers From Genetic Studiesmentioning
confidence: 99%
“…It has been shown that the maximum reduction of LV function has been associated with the following SNPs in those patients treated with trastuzumab: LDB2 (limb domain binding 2), BRINP1 (BMP/retinoic acid inducible neural-specific protein 1, a suppressor of cell cycle progression), RAB22A (a member of the RAS oncogene family which is key in endocytic trafficking), TRPC6 (transient receptor potential cation channel subfamily C member 6, involved in cardiac remodelling and hypertrophic cardiomyopathy), LINC01060 (a long intergenic noncoding RNA) and chromosome 6 intergenic region. Another GWAS involved a cohort of 385 patients identified targets which have been confirmed to be present in 181 patients [141]. This includes a SNP near PR domain containing 2, with ZNF domain (PRDM2), which is involved in DNA double-strand break and repair of oxidative stress.…”
Section: Insights On Potential New Biomarkers From Genetic Studiesmentioning
confidence: 99%
“…Variant rs12719020, associated with HFrEF, is located upstream (< 20 Kb) to COBL, a gene 235 related to vasculitis and type 1 diabetes 29 . For variants associated with HFpEF, rs12067046 is 236 located 500 Kb downstream of PLXNA2, which is related to the development of blood 237 vessel 30 and inflammatory-induced immune disorders 31 ; the linkage disequilibrium (LD) 238 block around rs12599260 is upstream (5 Kb) to HEATR3, which regulates inflammatory 239 immune response 32 ; rs149663839 is located upstream (50 Kb) to CAT, a key antioxidant 240 enzyme, which is hypothesized to play a role in the development of many chronic or late-241 onset diseases such as HF 33 ; ACTA1 (60 Kb to the LD block around rs114553497) and 242 CALD1 (5 Kb to rs10229703) are fundamental genes for skeletal/smooth muscle contraction 243 and had been linked to pulmonary hypertension in animal studies 34,35 ( Table 2 37 , and LV function 38 . Our 248 pathway-based analysis revealed five consistent pathways between HFrEF and HFpEF across 249 the two ethnicities ( Table 3).…”
Section: Identification Of Key Drivers For Hfpef and Hfref 197mentioning
confidence: 99%
“…CAMs, had been implicated previously in thromboembolic cardiovascular disease, type 2 254 diabetes, and LV function 25,38 . 255…”
Section: Identification Of Key Drivers For Hfpef and Hfref 197mentioning
confidence: 99%
“…In GWAS consisting of 1,695 cases of ACEi‐induced cough compared with 5,485 controls, SNPs in KCNIP4 were associated with increased risk for developing cough with ACEi. In recent GWAS, genetic variation has also been implicated as increasing susceptibility to anthracycline‐induced cardiotoxicity and reduced left ventricular function . Vancomycin, a commonly used antibiotic, is known to be nephrotoxic, with a GWAS suggesting variation at the chromosome 6q22.31locus could modulate that risk as well …”
Section: Gwas For Understanding Impact Of Genetic Variation On Drug Tmentioning
confidence: 99%
“…In recent GWAS, genetic variation has also been implicated as increasing susceptibility to anthracycline-induced cardiotoxicity and reduced left ventricular function. 67,68 Vancomycin, a commonly used antibiotic, is known to be nephrotoxic, with a GWAS suggesting variation at the chromosome 6q22.31locus could modulate that risk as well. 69…”
Section: Gwas For Understanding Impact Of Genetic Variation On Drug Tmentioning
confidence: 99%